A benefit of context reinstatement to recognition memory in aging: the role of familiarity processes. Issue 6 (2nd November 2017) - Ward, Emma V.; Maylor, Elizabeth A.; Poirier, Marie; Korko, Malgorzata; Ruud, Jens C. M.
ABSTRACT: Reinstatement of encoding context facilitates memory for targets in young and older individuals (e.g., a word studied on a particular background scene is more likely to be remembered later if it is presented on the same rather than a different scene or no scene), yet older adults are typically inferior at recalling and recognizing target–context pairings. This study examined the mechanisms of the context effect in normal aging. Age differences in word recognition by context condition (original, switched, none, new), and the ability to explicitly remember target–context pairings were investigated using word–scene pairs (Experiment 1) and word–word pairs (Experiment 2). Both age groups benefited from context reinstatement in item recognition, although older adults were significantly worse than young adults at identifying original pairings and at discriminating between original and switched pairings. In Experiment 3, participants were given a three-alternative forced-choice recognition task that allowed older individuals to draw upon intact familiarity processes in selecting original pairings. Performance was age equivalent. Findings suggest that heightened familiarity associated with context reinstatement is useful for boosting recognition memory in aging.